Negative electrode for nonaqueous electrolyte secondary battery

CN122930837APending Publication Date: 2026-10-16TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610239023.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-03
Filing Date
2026-02-28
Publication Date
2026-10-16

Smart Images

  • Figure CN122930837A_ABST
    Figure CN122930837A_ABST
Patent Text Reader

Abstract

A negative electrode for a nonaqueous electrolyte secondary battery includes, in order, a current collector, a first active material layer, and a second active material layer. The first active material layer and the second active material layer each contain a negative electrode active material. The negative electrode active material includes artificial graphite and natural graphite. The mass fraction of the artificial graphite in the first active material layer is higher than the mass fraction of the artificial graphite in the second active material layer. The mass fraction of the natural graphite in the first active material layer is lower than the mass fraction of the natural graphite in the second active material layer. The orientation angle of the negative electrode active material in the second active material layer is larger than the orientation angle of the negative electrode active material in the first active material layer. The orientation angle represents an acute angle formed by a long axis diameter of the negative electrode active material and a surface of the current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a negative electrode for a non-aqueous electrolyte secondary battery. Background Technology

[0002] Japanese Patent Application Publication No. 2009-064574 discloses a multilayer structure in which a first negative electrode layer near the negative electrode current collector is made of artificial graphite, and a second negative electrode layer away from the negative electrode current collector is made of natural graphite. Summary of the Invention

[0003] Hereinafter, the "negative electrode for non-aqueous electrolyte secondary batteries" will be simply referred to as the "negative electrode". A multilayer negative electrode structure is proposed. For example, artificial graphite is arranged in the lower layer near the negative electrode current collector, and natural graphite is arranged in the upper layer away from the negative electrode current collector. By arranging natural graphite, which has relatively good charging rate characteristics, near the positive electrode, it is expected that the charging rate characteristics can be improved. However, there is still room for further improvement in the charging rate characteristics.

[0004] The purpose of this invention is to improve charging rate characteristics.

[0005] The technical structure and effects of the present invention will be described below. However, the mechanism of action includes speculation. The mechanism of action does not limit the technical scope of the present invention.

[0006] 1. A negative electrode for a non-aqueous electrolyte secondary battery according to one aspect of the present invention comprises, in sequence, a current collector, a first active material layer, and a second active material layer. The first and second active material layers each contain a negative electrode active material. The negative electrode active material includes artificial graphite and natural graphite. The mass fraction of artificial graphite in the first active material layer is higher than that in the second active material layer. The mass fraction of natural graphite in the first active material layer is lower than that in the second active material layer. The orientation angle of the negative electrode active material in the second active material layer is greater than that in the first active material layer. The orientation angle represents the acute angle formed by the major axis diameter of the negative electrode active material and the surface of the current collector.

[0007] According to a new discovery of the present invention, by balancing the Li ion acceptability, electronic conductivity, and tortuosity in the thickness direction of the active material layer, it is expected that charging rate characteristics can be improved. In this invention, "toruosity" refers to the degree of tortuosity of the pores in the thickness direction of the active material layer. A smaller tortuosity is considered as the pores extending linearly along the thickness direction. Due to the smaller tortuosity, electrolyte diffusion in the thickness direction of the active material layer can be promoted.

[0008] Figure 1This is a conceptual cross-sectional view illustrating the first multilayer structure in this embodiment. In the accompanying drawings of the present invention, "NG" represents natural graphite. "AG" represents artificial graphite. "Li" represents Li ions. Circular elements represent unoriented active materials. Elliptical elements represent active materials oriented along the thickness direction. The degree of orientation is evaluated by the orientation angle. It is considered that the larger the orientation angle, the stronger the orientation of the particles in the thickness direction. The negative electrode 20 sequentially includes a current collector 21, a first active material layer 22a (lower layer), and a second active material layer 22b (upper layer). For example, it is possible to arrange artificial graphite "AG" in the first active material layer 22a and natural graphite "NG" in the second active material layer 22b. Compared with artificial graphite, natural graphite tends to have good Li ion acceptor properties. By arranging natural graphite in the upper layer, it is expected that the charging rate characteristics can be improved. However, in the first multilayer structure, since a balance between Li ion acceptor properties, electronic conductivity, and tortuosity cannot be achieved, the desired charging rate characteristics may not be obtained.

[0009] Figure 2 This is a conceptual cross-sectional view illustrating the second multilayer structure in this embodiment. As a method to reduce tortuosity, the negative electrode active material can be oriented along the thickness direction of the negative electrode. In the second multilayer structure, the negative electrode active material is oriented along the thickness direction in both the upper and lower layers. In the second multilayer structure, the tortuosity may become too small overall in the thickness direction. Furthermore, electron conduction between the current collector 21 and the lower layer, as well as within the lower layer, may be insufficient. In the second multilayer structure, a balance between Li ion acceptability, electron conductance, and tortuosity cannot be achieved, and therefore, the desired charging rate characteristics may not be obtained.

[0010] Figure 3 This is a conceptual cross-sectional view illustrating the third multilayer structure in this embodiment. In the third multilayer structure, the lower negative electrode active material (artificial graphite) is oriented along the thickness direction. The electrolyte permeates from the surface of the negative electrode 20 toward the interior. Due to the high tortuosity of the upper layer, the electrolyte may have difficulty passing through it. Due to insufficient supply of electrolyte to the lower layer, the acceptance of Li ions in the lower layer may become inactive. In the third multilayer structure, a balance between Li ion acceptability, electronic conductivity, and tortuosity cannot be achieved, and therefore the desired charging rate characteristics may not be obtained.

[0011] Figure 4This is a conceptual cross-sectional view illustrating the fourth multilayer structure in this embodiment. In the fourth multilayer structure, the upper negative electrode active material (natural graphite) is oriented along the thickness direction. The relatively strongly oriented natural graphite in the upper layer further promotes Li ion acceptance and is expected to promote the supply of electrolyte to the lower layer. The relatively weakly oriented synthetic graphite in the lower layer is expected to promote in-plane electron and ion conduction. As a result, throughout the negative electrode 20, the balance between Li ion acceptability, electron conductivity, and tortuosity is improved, and it is expected that the charging rate characteristics can be further improved.

[0012] 2. The negative electrode for a non-aqueous electrolyte secondary battery according to item "1" above may, for example, include the following configuration: The first active material layer and the second active material layer each further contain a binder. The mass fraction of the binder in the first active material layer is lower than the mass fraction of the binder in the second active material layer.

[0013] During the manufacturing process of the negative electrode, it is sometimes rolled. Rolling can cause the negative electrode active material on its surface to tilt laterally, thus reducing the orientation angle. Since the binder in the second active material layer has a relatively high mass fraction, it is expected that the negative electrode active material will not easily collapse.

[0014] 3. The negative electrode for a non-aqueous electrolyte secondary battery described in item "1" or "2" above may, for example, include the following configuration: The negative electrode for a non-aqueous electrolyte secondary battery sequentially comprises a current collector, a first active material layer, a binder layer, and a second active material layer. The mass fraction of the binder in the binder layer is higher than the mass fraction of the binder in the first and second active material layers.

[0015] The negative electrode active material expands during charging and contracts during discharging. Due to the different orientations of the negative electrode active material between the upper and lower layers, a mismatch in the expansion and contraction directions of the negative electrode active material may occur at the interface between the upper and lower layers. This mismatch in volume change may lead to interlayer delamination. The adhesive layer is expected to absorb this volume change mismatch and improve the adhesion between the upper and lower layers. It is anticipated that the adhesive layer will reduce interlayer delamination.

[0016] 4. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of "1" to "3" above may, for example, include the following configuration: The negative electrode active material in the first active material layer has a bimodal particle size distribution. The negative electrode active material in the second active material layer has a unimodal particle size distribution.

[0017] Because the lower layer of negative electrode active material is bimodal, the particles can be densely packed, thus improving the adhesion strength with the current collector is expected. Because the upper layer of negative electrode active material is unimodal, it is expected that fine pores along the thickness direction can be easily formed when the negative electrode active material is oriented along the thickness direction.

[0018] 5. In one embodiment of the present invention, the negative electrode for a non-aqueous electrolyte secondary battery sequentially comprises a current collector, a first active material layer, a binder layer, and a second active material layer. The first and second active material layers each contain a negative electrode active material and a binder. The negative electrode active material in the first active material layer has a bimodal particle size distribution. The negative electrode active material in the second active material layer has a unimodal particle size distribution. The mass fraction of the binder in the first active material layer is lower than that in the second active material layer. The negative electrode active material includes artificial graphite and natural graphite. Natural graphite has a larger aspect ratio than artificial graphite. The negative electrode active material in the first active material layer is substantially composed of artificial graphite. The negative electrode active material in the second active material layer is substantially composed of natural graphite. The orientation angle of the negative electrode active material in the second active material layer is larger than that of the negative electrode active material in the first active material layer. The orientation angle represents the acute angle formed by the major axis diameter of the negative electrode active material and the surface of the current collector. The mass fraction of the adhesive in the adhesive layer is higher than that in the first active material layer and the second active material layer.

[0019] Hereinafter, one embodiment of the present invention (hereinafter referred to as "this embodiment") will be described. However, this embodiment does not limit the technical scope of the present invention. This embodiment is illustrative in all respects. This embodiment is not limited. The technical scope of the present invention includes all modifications within the meaning and scope equivalent to the claims. For example, it is also intended to extract arbitrary configurations from this embodiment and combine them arbitrarily. Attached Figure Description

[0020] Hereinafter, with reference to the accompanying drawings, the features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described, in which the same reference numerals denote the same elements, and wherein:

[0021] Figure 1 This is a conceptual cross-sectional view representing the first multi-layer structure in this embodiment.

[0022] Figure 2 This is a conceptual cross-sectional view representing the second multi-layer structure in this embodiment.

[0023] Figure 3 This is a conceptual cross-sectional view representing the third multi-layer structure in this embodiment.

[0024] Figure 4 This is a conceptual cross-sectional view representing the fourth multi-layer structure in this embodiment.

[0025] Figure 5 This is a cross-sectional view illustrating the concept of the orientation angle in this embodiment.

[0026] Figure 6 This is a conceptual diagram illustrating an example of a non-aqueous electrolyte secondary battery in this embodiment.

[0027] Figure 7 This is a chart showing an example of the first particle size distribution in this embodiment.

[0028] Figure 8 This is a chart illustrating an example of the second particle size distribution in this embodiment. Detailed Implementation

[0029] Terms and statements

[0030] The terms "possessing," "including," and "having," and their variations, are open-ended expressions. A composition expressed in an open-ended manner may include additional elements besides the essential ones, or it may not include additional elements. The statement "composed of..." is a closed-ended expression. However, even a composition expressed in a closed-ended manner may include commonly impurities or additional elements unrelated to the target technology. The statement "substantially composed of..." is a semi-closed-ended expression. In a semi-closed-ended expression, it is permissible to add elements that do not substantially affect the fundamental and novel characteristics of the target technology.

[0031] Geometric terms should not be interpreted in a strict sense. As geometric terms, they may represent, for example, "parallel," "perpendicular," and "orthogonal." For instance, directions, angles, and distances can be relative to each other within a range where the same or similar functions can be achieved substantially. Geometric terms may also include tolerances and errors in design, operation, and manufacturing. The dimensional relationships in the drawings may sometimes differ from the actual dimensional relationships. To aid understanding, the dimensional relationships in the drawings may sometimes be altered. For example, length, width, and thickness may sometimes be changed. Sometimes, certain components may also be omitted.

[0032] "Artificial graphite" refers to graphite synthesized through artificial heat treatment. Artificial graphite is also known as synthetic graphite (SG). "Natural graphite" refers to graphite that occurs naturally in the environment. Natural graphite includes flake graphite. Flake graphite can be curled by bending the ends of its particles.

[0033] The "particle size" is determined by microscopy. The particle size is represented by the arithmetic mean of the long and short sides of the minimum bounding rectangle (MBR) of the particle's two-dimensional image. The "average particle size" is represented by the arithmetic mean of the particle sizes of 100 randomly selected particles. Furthermore, various image analyses in this embodiment can be performed using software. For example, software such as ImageJ can be used.

[0034] "Aspect ratio" refers to the ratio of the long side to the short side of the MBR. It is calculated using the arithmetic mean of the aspect ratios of 100 randomly selected particles.

[0035] Figure 5 This is a cross-sectional view illustrating the concept of the orientation angle in this embodiment. The "orientation angle" is the acute angle "θ" formed by the major axis diameter "L" of the particle and the surface of the current collector 21 in a cross-sectional scanning electron microscope (SEM) image of the negative electrode 20. The orientation angle can take values ​​from 0° to 90°. The major axis diameter represents the maximum Ferre diameter of the particle. The arithmetic mean of the orientation angles of 100 randomly selected particles is used.

[0036] "Basis Weight" refers to the mass per unit area.

[0037] Porosity is determined using image analysis. By binarizing the cross-sectional SEM images of each layer, voids and solids are distinguished. The porosity is calculated by dividing the total area of ​​the voids (total pixels) by the total area of ​​the layer.

[0038] The "active substance layer" is the collective term for the first and second active substance layers.

[0039] Non-aqueous electrolyte secondary battery

[0040] Figure 6This is a conceptual diagram illustrating an example of a non-aqueous electrolyte secondary battery according to this embodiment. The non-aqueous electrolyte secondary battery 100 may include, for example, a power generation element 50 and a housing 60. The housing 60 houses the power generation element 50. The housing 60 may be, for example, a metal container, a bag made of aluminum-plastic film, etc. The power generation element 50 may include, for example, a positive electrode 10, a negative electrode 20, a separator 30, and a non-aqueous electrolyte (not shown). The power generation element 50 may be, for example, a wound type or a stacked type. The power generation element 50 may have a unipolar structure or a bipolar structure. The separator 30 electrically isolates the positive electrode 10 from the negative electrode 20. The separator 30 may, for example, include a porous membrane made of resin. The non-aqueous electrolyte is a Li ion conductor. The non-aqueous electrolyte may, for example, include Li salts and organic solvents. The non-aqueous electrolyte may, for example, be impregnated in the separator 30. The non-aqueous electrolyte may, for example, include polymer electrolytes, gel electrolytes, solid electrolytes, etc. Solid electrolytes may, for example, include sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes, etc. The positive electrode 10 contains a positive electrode active material. This active material may include, for example, lithium transition metal composite oxides (Li[NiCoMn]O2), lithium phosphate compounds (Li[FeMn]PO4), etc. Furthermore, the description of [NiCoMn], [FeMn], etc., indicates that the total composition ratio of the components within the brackets is "1". As long as the total is 1, the composition ratio of each component is arbitrary. For example, the composition ratio of some components may be zero.

[0041] negative electrode

[0042] The negative electrode 20 can be, for example, in sheet form. The negative electrode 20 has a fourth layer structure ( Figure 4 The negative electrode 20 includes, in the thickness direction, a current collector 21, a first active material layer 22a, and a second active material layer 22b. The active material layers may be disposed on a portion of the surface of the current collector 21 or on the entire surface. The active material layers may be disposed on only one side of the current collector 21 or on both sides of the current collector 21. The current collector 21 may, for example, include a metal foil (Cu foil, Ni foil, etc.), a conductive resin layer, etc. The current collector 21 may, for example, have a thickness from 1 μm to 100 μm.

[0043] The negative electrode 20 may include any other components as long as it sequentially comprises a current collector 21, a first active material layer 22a, and a second active material layer 22b. For example, the negative electrode 20 may sequentially comprise a current collector 21, a first active material layer 22a, a binder layer 22c, and a second active material layer 22b. For example, a conductive layer or a sealing layer (not shown) may be disposed between the first active material layer 22a and the current collector 21. For example, a ceramic particle layer (not shown) may be disposed on the surface of the second active material layer 22b. The ceramic particle layer may include, for example, heat-resistant ceramics (alumina, boehmite).

[0044] The layers included in the negative electrode active material layer 22 can be, for example, coating layers. A coating layer refers to a layer formed by applying a coating material. The coating materials can be applied substantially simultaneously or sequentially. For example, before the coating material dries, by applying a magnetic field to the coating layer, the negative electrode active material contained in the coating layer can be oriented along the thickness direction. For example, the orientation angle can be adjusted by the strength of the magnetic field, the concentration of the coating material, the pressing pressure, etc.

[0045] Each layer can have any thickness. For example, the thickness "T1" of the first active material layer 22a and the thickness "T2" of the second active material layer 22b can satisfy relationships such as "T1 / T2 = 1 / 9 to 9 / 1", "T1 / T2 = 2 / 8 to 8 / 2", "T1 / T2 = 3 / 7 to 7 / 3", and "T1 / T2 = 4 / 6 to 6 / 4". The thickness "T1" can be, for example, 10 μm or more, 50 μm or more, 100 μm or more, 200 μm or more, or 500 μm or more. The thickness "T1" can also be, for example, less than 1 mm, less than 500 μm, or less than 200 μm.

[0046] Each layer can have any weight per unit area. For example, the weight per unit area "W1" of the first active material layer 22a and the weight per unit area "W2" of the second active material layer 22b can satisfy relationships such as "W1 / W2 = 1 / 9 to 9 / 1", "W1 / W2 = 2 / 8 to 8 / 2", "W1 / W2 = 3 / 7 to 7 / 3", and "W1 / W2 = 4 / 6 to 6 / 4". The weight per unit area "W1" can be, for example, 1 mg / cm³. 2 Above, 5mg / cm 2 Above, 10mg / cm 2 Above or 20 mg / cm 2 The above. The weight per unit area "W1" can be, for example, 50 mg / cm³. 2 Below, 30mg / cm 2 Below, 25mg / cm 2 Below, 15mg / cm 2 Below or 10 mg / cm 2 the following.

[0047] The porosity of the active material layer can be approximately constant throughout the entire region. However, the porosity of the active material layer can vary locally. For example, the porosity "φ1" of the first active material layer 22a can be lower than the porosity "φ2" of the second active material layer 22b. That is, the relationship "φ1 < φ2" and "1 < φ2 / φ1" can be satisfied. The ratio "φ2 / φ1" can be, for example, 1.2 or higher, 1.5 or higher, 2 or higher, or 2.5 or higher. The ratio "φ2 / φ1" can be, for example, 5 or lower, 3 or lower, or 2 or lower.

[0048] Negative electrode active material

[0049] The first active material layer 22a and the second active material layer 22b each contain a negative electrode active material. Each active material layer may also contain, for example, conductive materials, binders, etc. Each active material layer may independently include, for example, 0% to 10% binder, 0% to 10% conductive material, and the remainder negative electrode active material by mass fraction. The mass fraction of binder and conductive material in each active material layer may be independently 0.1% to 3% or 0.5% to 2%.

[0050] Negative electrode active materials include artificial graphite and natural graphite. Besides artificial and natural graphite, other active materials can also be included. These other active materials may include, for example, Si, SiO, lithium titanate, Sn-based alloys, SnO, pure Li, and Li-based alloys.

[0051] The artificial graphite is concentrated in the first active material layer 22a. The mass fraction of artificial graphite in the first active material layer 22a is "M". 1A "The mass fraction of artificial graphite higher than that in the second active material layer 22b" M 2A That is, satisfying "M" 2A <M 1A “1 < M” 1A / M 2A The relationship is "". It is more related to "M". 1A / M 2A "For example, it can be 1.5 or higher, 2 or higher, 3 or higher, 5 or higher, 10 or higher, 50 or higher, or 100 or higher. Compared to 'M'..." 1A / M 2A "For example, it can be below 1000 or below 100. Mass fraction" M 1A "For example, it can be 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, 95% or more, 98% or more, or 99% or more. Quality fraction "M" 1A "For example, it can be below 100%, below 99%, below 98%, or below 95%."

[0052] Natural graphite is concentrated in the second active material layer 22b. The mass fraction of natural graphite in the first active material layer 22a is "M". 1N "The mass fraction of natural graphite below that in the second active material layer 22b" M 2N That is, satisfying "M" 1N <M 2N “M” 1N / M 2N The relationship is <1. Compared to "M" 1N / M 2N"For example, it can be below 0.9, below 0.5, below 0.3, below 0.1, or below 0.01. Compared to 'M'..." 1N / M 2N "For example, it can be above 0, above 0.001, above 0.01, or above 0.1. Mass fraction "M" 2N "For example, it can be 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, 95% or more, 98% or more, or 99% or more. Quality fraction "M" 2N "For example, it can be below 100%, below 99%, below 98%, or below 95%."

[0053] As mentioned above, as long as "M" is satisfied 2A <M 1A "and M" 1N <M 2N Given the relationship between the first active material layer 22a and the second active material layer 22b, they can each independently contain artificial graphite, natural graphite, and other active materials. For example, the negative electrode active material in the first active material layer 22a can be substantially composed of artificial graphite and Si-based active materials. The negative electrode active material in the second active material layer 22b can be substantially composed of natural graphite.

[0054] Both synthetic and natural graphite can independently possess arbitrary particle shapes. Particle shapes can be, for example, spherical, ellipsoidal, or flat. For instance, the aspect ratio of natural graphite is "R". N "It can have an aspect ratio greater than that of artificial graphite" R A For example, it can satisfy "1 < R". N / R A Relationships such as ≤5. The aspect ratio of natural graphite is "R". N "For example, it can be 1.5 or higher, 2 or higher, or 3 or higher. The aspect ratio of natural graphite is 'R'." N "For example, it can be below 5. The aspect ratio of artificial graphite is "R". A "For example, it can be less than 1.5, 1.4 or less, 1.3 or less, 1.2 or less, or 1.1 or less. The aspect ratio of artificial graphite is 'R'." A "For example, it can be 1 or more."

[0055] Between the first active material layer 22a and the second active material layer 22b, the orientation of the negative electrode active material differs. The orientation angle "θ2" of the negative electrode active material in the second active material layer 22b is greater than the orientation angle "θ1" of the negative electrode active material in the first active material layer 22a. That is, the relationship "θ1 < θ2" is satisfied. The orientation angle "θ2" can be, for example, 30° or more, 45° or more, 60° or more, or 75° or more. The orientation angle "θ2" can be, for example, less than 90°, less than 75°, or less than 60°. The orientation angle "θ1" can be, for example, less than 30°, less than 15°, or less than 5°. The orientation angle "θ1" can be, for example, 0° or more.

[0056] Both artificial and natural graphite can independently have arbitrary average particle sizes. For example, the average particle size can be 1 μm or more, 5 μm or more, 10 μm or more, or 15 μm or more. Alternatively, the average particle size can be 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less.

[0057] The particle size distribution may differ between the first active material layer 22a and the second active material layer 22b. The particle size distribution can be based on volume or number. In this embodiment, in the histogram, a convex region with a height at least 0.1 times the height of the maximum peak is considered a peak. The number of peaks can be, for example, one or more, two or more, or three or more. "Single-peak type (also called single-modal type)" indicates a distribution with essentially one peak. "Bimodal type" indicates a distribution with essentially two peaks. "Multimodal type" indicates a distribution with three or more peaks.

[0058] Figure 7 This is a graph illustrating an example of the first particle size distribution in this embodiment. The negative electrode active material in the first active material layer 22a can have the first particle size distribution. The first particle size distribution is bimodal. The peak on the side with the larger particle size has a mode diameter "d". 1L "Mode diameter (most frequent value)" represents the particle size corresponding to the peak. The mode diameter "d" can also be expressed as... 1L "Consider it as the average particle size of the large particle group. The peak on the side with the smaller particle size has the mode diameter 'd'." 1S The pattern diameter "d" can also be used. 1S "This is considered the average particle size of the small particle group. The ratio of the large particle size to the small particle size is 'd'." 1L / d 1S "For example, it can be 2 or more, 3 or more, 4 or more, or 5 or more. The ratio of large particle size to small particle size is 'd'." 1L / d 1S "For example, it can be below 10, below 8, or below 6."

[0059] Figure 8This is a graph illustrating an example of the second particle size distribution in this embodiment. The negative electrode active material in the second active material layer 22b may have a second particle size distribution. The second particle size distribution is unimodal. The peak has a pattern diameter "d2". The pattern diameter "d2" can also be regarded as the average particle size of the negative electrode active material in the second active material layer 22b.

[0060] In the first particle size distribution ( Figure 7 ) and the second particle size distribution ( Figure 8 Between ), for example, it can satisfy "d" 1S <d2<d 1L “d” 1S <d 1L <d2”, d2<d 1S <d 1L These relationships, for example, can be satisfied to improve the balance between Li ion acceptability, electronic conductivity, and tortuosity.

[0061] adhesives

[0062] Adhesives may include, for example, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), etc. The mass fraction of the adhesive can remain substantially constant throughout the entire region of the active material layer. However, the mass fraction of the adhesive may vary locally. For example, the mass fraction of the adhesive may differ between the first active material layer 22a and the second active material layer 22b. For instance, the mass fraction of the adhesive in the first active material layer 22a may be "M". 1B "The mass fraction of the adhesive in the second active material layer 22b can be lower than that in the second active material layer 22b." 2B That is, it can satisfy "M". 1B <M 2B “1 < M” 2B / M 1B The relationship is "". It is more related to "M". 2B / M 1B "For example, it can be 1.2 or higher, 1.5 or higher, 2 or higher, 2.5 or higher. Compared to 'M'..." 2B / M 1B "For example, it can be 3 or less or 2 or less."

[0063] For example, an adhesive layer 22c may be formed between the first active material layer 22a and the second active material layer 22b. The mass fraction of the adhesive in the adhesive layer 22c is higher than the mass fraction of the adhesive in the first active material layer 22a and the second active material layer 22b. The adhesive layer 22c may be a layer that substantially does not contain any negative electrode active material. The adhesive layer 22c may, for example, contain 0% to 10% conductive material and the remainder adhesive by mass fraction. The mass fraction of the conductive material in the adhesive layer 22c may, for example, be 1% to 5%.

[0064] For example, the types of adhesives between the layers can be the same. Alternatively, the types of adhesives between the layers can be different. For example, the adhesive in adhesive layer 22c can contain a resin that swells due to the electrolyte. For example, the adhesive in adhesive layer 22c can contain an ion-permeable resin, an ion-conducting resin, etc. By permeating adhesive layer 22c with the electrolyte and Li ions, it is expected to improve the charging rate characteristics. For example, the adhesive in adhesive layer 22c can include a fibrous resin. The fibrous resin can be extended in a manner that crosslinks the first active material layer 22a and the second active material layer 22b. Crosslinking the first active material layer 22a and the second active material layer 22b with the fibrous resin, for example, is expected to improve the peel strength, etc. The adhesive in adhesive layer 22c can, for example, include at least one selected from the group consisting of PAA, polyacrylate, CMC, alginate, polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), and PTFE. For example, PAA, PVDF, and PVDF-HFP can exhibit swelling properties, ion permeability, and ion conductivity. For example, PTFE can be in fibrous form.

[0065] The thickness "T3" of the adhesive layer 22c can, for example, be less than the thickness "T1" of the first active material layer 22a and the thickness "T2" of the second active material layer 22b. The thickness "T3" of the adhesive layer 22c can, for example, be less than 10 μm, less than 5 μm, or less than 3 μm. The thickness "T3" of the adhesive layer 22c can, for example, be more than 0.5 μm, more than 1 μm, or more than 3 μm. The area weight "W3" of the adhesive layer 22c can, for example, be less than the area weight "W1" of the first active material layer 22a and the area weight "W2" of the second active material layer 22b. The area weight "W3" of the adhesive layer 22c can, for example, be 5 mg / cm³. 2 Below, 3mg / cm 2 Below or 1 mg / cm 2 The following is an example of the adhesive layer 22c, where the unit area weight "W3" can be 0.1 mg / cm³. 2 Above or 0.5 mg / cm 2 above.

[0066] conductive materials

[0067] Conductive materials may include, for example, acetylene black, carbon nanotubes (CNTs), and vapor-grown carbon fibers (VGCF). The mass fraction of the conductive material can remain approximately constant throughout the entire region of the active material layer. However, the mass fraction of the conductive material may vary locally. For example, the mass fraction of the conductive material may differ between layers. For example, the types of conductive materials may differ between layers. For example, the adhesive layer 22c may contain a fibrous conductive material. The adhesive layer 22c may, for example, contain at least one material selected from the group consisting of CNTs and VGCF. The fibrous conductive material may be extended in a manner that crosslinks the first active material layer 22a and the second active material layer 22b. Crosslinking the first active material layer 22a and the second active material layer 22b with the fibrous conductive material is expected to, for example, improve charging rate characteristics and reduce interlayer delamination.

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, characterized in that, It consists of a current collector, a first active material layer, and a second active material layer, in sequence. The first active material layer and the second active material layer each contain a negative electrode active material. The negative electrode active material includes artificial graphite and natural graphite. The mass fraction of artificial graphite in the first active material layer is higher than the mass fraction of artificial graphite in the second active material layer. The mass fraction of natural graphite in the first active material layer is lower than the mass fraction of natural graphite in the second active material layer. The orientation angle of the negative electrode active material in the second active material layer is greater than the orientation angle of the negative electrode active material in the first active material layer, and The orientation angle refers to the acute angle formed by the major axis diameter of the negative electrode active material and the surface of the current collector.

2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that, The first active material layer and the second active material layer each further contain an adhesive, and The mass fraction of the adhesive in the first active material layer is lower than the mass fraction of the adhesive in the second active material layer.

3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 2, characterized in that, It sequentially includes the current collector, the first active material layer, the adhesive layer, and the second active material layer, and The mass fraction of the adhesive in the adhesive layer is higher than the mass fraction of the adhesive in the first active material layer and the second active material layer.

4. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that, The negative electrode active material in the first active material layer has a bimodal particle size distribution, and The negative electrode active material in the second active material layer has a unimodal particle size distribution.

5. A negative electrode for a non-aqueous electrolyte secondary battery, characterized in that, It comprises, in sequence, a current collector, a first active material layer, an adhesive layer, and a second active material layer. The first active material layer and the second active material layer respectively contain a negative electrode active material and a binder. The negative electrode active material in the first active material layer has a bimodal particle size distribution. The negative electrode active material in the second active material layer has a unimodal particle size distribution. The mass fraction of the adhesive in the first active material layer is lower than the mass fraction of the adhesive in the second active material layer. The negative electrode active material includes artificial graphite and natural graphite. The natural graphite has a larger aspect ratio than the artificial graphite. The negative electrode active material in the first active material layer is essentially composed of the artificial graphite. The negative electrode active material in the second active material layer is essentially composed of the natural graphite. The orientation angle of the negative electrode active material in the second active material layer is greater than the orientation angle of the negative electrode active material in the first active material layer. The orientation angle refers to the acute angle formed by the major axis diameter of the negative electrode active material and the surface of the current collector, and The mass fraction of the adhesive in the adhesive layer is higher than the mass fraction of the adhesive in the first active material layer and the second active material layer.

Citation Information

Patent Citations

  • Lithium-ion secondary battery

    JP2009064574A